The Revival of al-Farabi’s Ethical Idea: Virtue and the Spiritual Foundations of Turkic-Islamic Civilization - Baizhuma, Samet; Meirbayev, Bekzhan; Baitenova, Nagima; Lokman, Ainul Asyraf (Journal of Al-Tamaddun, 2025)
This article examines Abu Nasr al-Farabi’s ethical and political philosophy as a foundational framework for the formation of virtuous personality and leadership within Turkic-Islamic intellectual history. Rather than treating virtue as an abstract moral ideal, al-Farabi conceptualizes faḍīla as a structured synthesis of rational knowledge, moral habituation, and spiritual discipline oriented toward saʿāda (human happiness). The study focuses on al-Farabi’s doctrine of the virtuous person and the virtuous ruler as articulated primarily in The Virtuous City and traces its reception and transformation in the works of later Turkic thinkers, including Yusuf Balasaguni, Khoja Ahmad Yasawi, Mahmud Kashgari, and Ahmad Yugnaki. It shows that al-Farabi’s doctrine of the virtuous person and ruler can be understood as a civilizational model in which personal moral growth and the welfare of society are indivisibly united. Employing analytical-historical and comparative philosophical methods, the article examines how al-Farabi’s model of ethical leadership was reinterpreted within different intellectual and socio-spiritual contexts, particularly through juridical, pedagogical, and Sufi frameworks. This approach enables the identification of the ethical, intellectual, and spiritual dimensions of al-Farabi’s system and their transformation within later Turkic-Islamic thought. The analysis demonstrates that, despite variations in form and emphasis, these thinkers preserve a shared conception of leadership grounded in moral self-perfection, justice, and responsibility toward the community. The findings indicate that Turkic-Islamic ethical thought not only inherited al-Farabi’s ideas but also adapted them into a durable civilizational paradigm linking personal moral development with social order. By situating al-Farabi within this intellectual continuum, the article clarifies his enduring significance for Islamic moral philosophy and provides a historically grounded perspective on virtue-based leadership and ethical education.